Effects of palladium loading on the response of a thick film flame-made ZnO gas sensor for detection of ethanol vapor - Liewhiran C. (2014)
ZnO nanoparticles doped with 0-5 mol% Pd were successfully produced in a single step by flame spray pyrolysis (FSP) using zinc naphthenate and palladium (II) acetylacetonate dissolved in toluene-acetonitrile (80:20 vol%) as precursors. The effect of Pd loading on the ethanol gas sensing performance of the ZnO nanoparticles and the crystalline sizes were investigated. The particle properties were analyzed by XRD, BET, AFM, SEM (EDS line scan mode), TEM, STEM, EDS, and CO-pulse chemisorption measurements. A trend of an increase in specific surface area of samples and a decrease in the dBET with increasing Pd concentrations was noted. ZnO nanoparticles were observed as particles presenting clear spheroidal, hexagonal and rod-like morphologies. The sizes of ZnO spheroidal and hexagonal particle crystallites were in the 10-20 nm range. ZnO nanorods were in the range of 10-20 nm in width and 20-50 nm in length. The size of Pd nanoparticles increased and Pd-dispersion% decreased with increasing Pd concentrations. The sensing films were produced by mixing the particles into an organic paste composed of terpineol and ethyl cellulose as a vehicle binder. The paste was doctor-bladed onto Al2O3 substrates interdigitated with Au electrodes. The film morphology was analyzed by SEM and EDS analyses. The gas sensing of ethanol (25-250 ppm) was studied in dry air at 400°C. The oxidation of ethanol on the sensing surface of the semiconductor was confirmed by MS. A well-dispersed of 1 mol%Pd/ZnO films showed the highest sensitivity and the fastest response time (within seconds). © 2007 by MDPI.